miR-203 Inhibits Alcohol-Induced Hepatic Steatosis by Targeting Lipin1 - Cheng, Xiao-Yu; Liu, Jun-Da; Lu, Xin-Yi; Yan, Xing; Huang, Cheng; Meng, Xiao-Ming; Li, Jun (Frontiers in Pharmacology, 2018)
Alcoholic liver disease (ALD) is a global liver disease which characterized by liver inflammation, fatty liver, alcoholic hepatitis, or liver cirrhosis. Alcohol abuse is one of the main reasons for liver disease. Alcoholic fatty liver (AFL) disease is the early stage of ALD and associated with the excessive lipids accumulation in hepatocytes as well as oxidative stress. MicroRNA-203 (miR-203) is known to suppress the proliferation and metastasis of hepatocellular carcinoma, but the role in the progression of alcoholic liver disease is not clear and is warranted for further investigation. In the present study, we have found the expression of miR-203 is down-regulated in Gao-Binge alcoholic mice model and ethanol-induced AML-12 cell lines in vitro. Furthermore, over-expression of miR-203 decrease the lipids accumulation in liver and ethanol-induced AML-12 cells. Mechanistically, we identified that Lipin1 is a key regulator of hepatic lipid metabolism, and acts as a downstream target for miR-203. In summary, our results suggested that over-expression of miR-203 inhibited the liver lipids accumulation and the progression of AFL by targeting Lipin1.